Parametric and nonparametric statistics for sample surveys and customer satisfaction data. ([2018]) - Arboretti, Rosa; Bathke, Arne; Bonnini, Stefano; Bordignon, Paolo; Carrozzo, Eleonora; Corain, Livio; Salmaso, Luigi
No abstract available